2013
DOI: 10.1002/grl.50492
|View full text |Cite
|
Sign up to set email alerts
|

Rock varnish evidence for a Younger Dryas wet period in the Dead Sea basin

Abstract: [1] Rock varnish from 14.6 to 13.2 ka recessional shorelines of late glacial Lake Lisan and fan delta surfaces between 280 and 365 m bmsl (meters below mean sea level) along the western margins of the Dead Sea contains replicable layering patterns, characterized by a low Mn and Ba orange/yellow surface layer and a high Mn and Ba dark basal layer. The deposition of the dark basal layers immediately after the lake recession represents a wet period coinciding with the Younger Dryas (YD) cooling (12.9-11.6 ka), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…1D; ref. 9) and the formation of a dark manganese and barium oxide desert varnish crust on the paleo-lakeshore pebbles (6). These results also help to resolve some discrepancies in recent reconstructions of the YD.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…1D; ref. 9) and the formation of a dark manganese and barium oxide desert varnish crust on the paleo-lakeshore pebbles (6). These results also help to resolve some discrepancies in recent reconstructions of the YD.…”
Section: Discussionmentioning
confidence: 67%
“…1). Vastly disparate interpretations of the environmental and climatic impact of the YD on the southern Levant have been proposed with some arguing for xeric and others for opposing mesic conditions (3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The layering typical of clay minerals in HRTEM views of varnish [67] is being broken apart by the dissolution and then the reprecipitation of the Mn-rich granules into the clays-to the point where the layered texture is mostly lost (Figure 9c). These nanoscale movements do not create instability in the varnish laminations seen at the micron scale that are stable for tens of millennia [131][132][133]. Scale matters and these snanoscale movements would be analogous to cars shuffling in a parking structure composed of micron-scale laminations.…”
Section: Nanoscale Observations Of Rock Coatingsmentioning
confidence: 99%
“…mass eruption rate was 1,000× that of the weak plume: 1.5× 10 9 kg s -1 (e.g., Suzuki and Koyaguchi, 2009). The atmospheric conditions were based on the reanalysis data obtained from European Centre for Medium-Range Weather Forecasts (ECMWF) by Costa et al (2013) for Pinatubo volcano at 13:40 PLT of 15 June 1991 (the profiles are shown in Fig. 1B in Costa et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%